Strength of a New All-Ceramic Restorative Material “Turkom-Cera” Compared to Two Other Alumina-Based All-Ceramic Systems - AL-Makramani, Bandar M. A.; Abu-Hassan, Abdul A. A. Razak and Mohamed I. (IntechOpen, 2011)
None